Characteristic of Levels of Forming of Ukrainian-Speaking Dialogue Competence of the Pupils of 10-11 Forms of General Schools - Maryna Hrudok-Kostiushko (Pedagogical Discourse, 2012)
Characteristic of levels of forming of Ukrainian-speaking dialogue competence of the pupils of 10-11 forms of general schools is offered in the article, external and internal factors, influencing the effectiveness of forming of Ukrainian-speaking dialogue competence are presented.